Metaphor as an object naming tool in the Mfantse dialect of Akan (Nordic Journal of African Studies, 2021)
This article discusses the use of metaphor in Akan (Mfantse) object names from an onomasiological point of view. Metaphors in naming have received little attention in the Akan literature on naming, but they play an important role in the formation of new object naming units among the Akan (Mfantse) people. They draw on resemblances in salient features such as shape, tactile, gustatory, function, projection and arrangement. They also draw on how the Mfantse people perceive and conceptualize certain features in their environment. The article concludes that in the naming of referents, metaphor is used to economize naming forms and to achieve effability in situations where literal description fails. It is used as a basic naming tool and is not only a creative venture in Mfantse. The article contributes to the study of names by dealing with the various principles in object naming, whereas most previous studies of names in Akan and related languages have dealt primarily with personal names, which are created using different principles.